SUPERVISION AND ENFORCEMENT OF IMMIGRATION FOR FOREIGNERS WHO COMMIT VIOLATIONS IN INDONESIAN TERRITORY - Fajar Harry Murcahyo; Subekti Subekti (EQUALEGUM International Law Journal, 2023)
Background. The issue of supervision of foreigners plus illegal immigrants is a very sensitive issue in the Asia Pacific region because it involves many countries and is cross-border in nature. The use of Visa-Free Visit Permits is a modus operandi for foreigners to stay in Indonesian territory and then commit immigration violations which include misuse of stay permits, overstay, illegal immigrants, use of fake travel documents, cybercrime. The research purpose was to determine supervision and enforcement of immigration by immigration officer for foreigners who commit violations in the territory of Indonesia. Research Method. This research was a normative legal research. Sources of legal materials used are primary and secondary legal materials. The legal materials obtained will be analyzed using a qualitative analysis method, namely an analysis that departs from the norms, principles that exist as positive legal norms which are then analyzed qualitatively with the understanding that the results of the analysis will be realized in the form of descriptions not in the form of numbers. Findings. The supervision of foreigners is carried out in the form of administrative, coordinative and on-site supervision with one field operation. The actions taken are refusal to grant visa, refusal to allow entry into Indonesian territory, change, limit/ cancel immigration permit, prohibit foreigners to be in a certain place in Indonesian territory. Conclusion. In the event of a criminal offense, immigration may conduct process of criminal procedure law. In certain cases, immigration may take immigration action directly such as expulsion or deportation.